High Night Temperature and Abscisic Acid Affect Rice Productivity through Altered Photosynthesis, Respiration and Spikelet Fertility. Issue 6 (1st November 2013) - Mohammed, R.; Cothren, J. T.; Tarpley, L.
ABSTRACT: High night temperature (HNT) is among the important abiotic stresses limiting rice production. The impacts of abscisic acid (ABA) on higher plants have been the subject of many studies. However, little or no work has been performed on rice responses to ABA under HNT‐stress conditions. This study determined the effects of ABA on rice leaf photosynthetic rate (PN ), photochemistry, respiration, and physiology under HNT. Plants were grown under ambient night temperature (ANT; 25°C) or HNT (30°C) with or without ABA (100 ppm) application from the boot stage of rice plants until harvest. The HNT decreased rice yield (11%), which was associated with decreasing PN (5%), pollen viability (11%), and spikelet fertility (5%) and increasing respiration rate (44%). In addition, HNT decreased grain width (4%) and increased grain chalkiness (65%), thereby decreasing grain quality. The ABA‐treated plants showed increased yield (15%) as a result of increased PN (6%) and spikelet fertility (6%) and decreased respiration (33%), under HNT. The increased PN under HNT as a result of ABA application is associated with increased stomatal conductance (22%) and decreased nonphotochemical quenching (NPQ; 29%). In addition, ABA‐treated plants grown under ANT also showed increased yield (9%) as a result of increased PN (7%) and spikelet fertility (7%) and decreased respiration (16%). The increased PN under ANT as a result of ABA application was due to increased quantum yield (8%) and electron transport rate (8%). This study shows that exogenous application of ABA has the potential to increase rice yields under HNT.